Conductive Nanocomposite Hydrogels for Neural Tissue Engineering: A Systematic Scoping Review of Recent Trends - Moghaddasi, Mohammad; Oktay, Busra; Bingol, Ayse Betul; Yanikoglu, Reyhan; Muslu, Meryem; Ozbolat, Ibrahim T.; Ustundag, Cem Bulent (WILEY, 2025)
Conductive nanocomposite hydrogels (CNHs) represent a promising tool in neural tissue engineering, offering tailored electroactive microenvironments to address the complex challenges of neural repair. This systematic scoping review, conducted in accordance with PRISMA-ScR guidelines, synthesizes recent advancements in CNH design, functionality, and therapeutic efficacy for central and peripheral nervous system (CNS and PNS) applications. The analysis of 125 studies reveals a growing emphasis on multifunctional materials, with carbon-based nanomaterials (CNTs, graphene derivatives; 36.8%), metals (Iron oxides, gold, etc.; 24.0%), conductive polymers (PEDOT, PPy, etc.; 16.0%), and hybrid systems dominating due to their synergistic electrical, mechanical, and bioactive properties. For CNS repair, spinal cord injury models (n = 42) leverage antioxidant-conductive hybrids and immunomodulatory systems to mitigate oxidative stress and neuroinflammation. For PNS repair-particularly sciatic nerve regeneration (n = 20)-CNHs demonstrate efficacy through stimuli-responsive strategies (including wireless and self-powered piezoelectric and magnetic systems) and biomimetic scaffold design to guide axonal regeneration. Tailored hydrogel designs also address traumatic brain injury, stroke, and Parkinson's disease. Beyond these, CNHs show promise in diverse neural tissue engineering contexts, including neurovascular niche reconstruction for diabetic wound healing, coordinated neurogenic and osteogenic differentiation in bone and muscle repair, and auditory neurogenesis in cochlear applications. This review highlights the potential of CNHs by elucidating recent applications across various neural tissue engineering contexts.
Keywords: conductive hydrogel; nanocomposite; nanomaterial; neural differentiation; neural tissue engineering; STEM-CELLS; NEURITE OUTGROWTH; DIFFERENTIATION; REGENERATION; MECHANOTRANSDUCTION; NANOMATERIALS; SCAFFOLDS; CONDUITS; REPAIR; ROLES; Chemistry; Science & Technology - Other Topics; Materials Science